Resolving mandibular arch discrepancy through utilization of leeway space - Matrishva B Vyas; Navin Hantodkar (Wolters Kluwer Medknow Publications, 2011)
Space management through utilization of leeway space represents one of the most critical aspects of interceptive orthodontic treatment in mixed dentition based on its potential to prevent crowding in the permanent dentition. Lingual arch is the most frequently used space maintaining device for preserving leeway. Case reports of patients in whom potential space discrepancy in mandibular arch was managed through preservation and utilization of leeway space are presented.